Medicinskoe soprovoždenie futbol'nych arbitrov: sostojanie i perspektivy - Bachrach, I. I.; Grec, G. N.; Budogosskij, A. D.; Novoselov, E. A. M; Turbin, E. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
The article covers an actual problem of medical supervision of the professional football referees and students of the education centers (academies, schools). Need for improvement of normative acts in this field is substantiated. The project of the legal act concerning the supervision of football referees who are judging both professional and amateur competitions as well as education centers students is described.